Antu language in the Sangin oral narrative of the Sihans in Sarawak - Noriah, Mohamed; Jamilah Bebe, Mohamad; Mohd Tarmizi, Hasrah (Penerbit Universiti Sains Malaysia, 2021)
This article discusses the Sihan community and one of their traditional oral narratives, known as sangin. Sihan is an indigenous ethnic group residing in Belaga, Sarawak, Malaysia, and sangin is an activity that can be considered a folklore, narrative in manner, and performed for entertainment and native remedy. Data on the community in this study was obtained through interviews with 71 Sihan informants in Belaga, Sarawak, Malaysia. The sangin by one of its practitioners was recorded during the community's leisure activities. The recorded sangin song, delivered in the style of storytelling, narrated for entertainment, not for remedy purposes. The description of the sangin indicates that the language in the oral tradition, called antu language (language of the spirit) is very different from the modern, every day Sihan language used by its speakers. In terms of usage, sangin can be considered extinct because of the reduced number of Sihan speakers (only 218 left) and lessening number of sangin practitioners (only three remain). Sangin as a native remedy no longer has a place in the community with the availability of modern medical treatment, the mass migration of the Sihans from their original area, and the change in the Sihans' life style, from nomadic to community life.